2015
DOI: 10.1039/c5ra15187b
|View full text |Cite
|
Sign up to set email alerts
|

Poly(ω-bromoalkylnorbornenes-co-norbornene) by ROMP-hydrogenation: a robust support amenable to post-polymerization functionalization

Abstract: ARTICLEThis journal is © The Royal Society of Chemistry 2013 J. Name., 2013 Rodrigo García-Loma and Ana C. Albéniz*The ring opening metathesis copolymerization of norbornene and ω-bromoalkylnorbornenes NB-(CH2)nBr (n = 1, 4) by Grubbs' 2nd generation catalyst, followed by hydrogenation, gives insoluble saturated polynorbornenes (ROMPH-PNBs) that have pendant ω-bromoalkyl chains (4a, b). These materials can be functionalized by nucleophilic substitution of bromide to give a variety of substituted polymers (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 108 publications
0
12
0
Order By: Relevance
“…The saturated polymer backbone in VA‐PNBs has a clear advantage compared with ring‐opening metathesis polymerization (ROMP)‐PNBs (Figure ), especially in metal‐catalyzed reactions. Recently, we have reported the risks of exposing the unsaturated ROMP scaffold to some metal complexes, and we have observed the insertion of the C=C double bond of ROMP‐PNB into a palladium–aryl complex, leading to the formation of an aryl‐substituted polymer . Considering the a priori attractive features of VA‐PNBs, we decided to test the behavior of the VA‐PNB skeleton as a support for palladium complexes in two cross‐coupling reactions, namely Suzuki and Negishi couplings.…”
Section: Introductionmentioning
confidence: 99%
“…The saturated polymer backbone in VA‐PNBs has a clear advantage compared with ring‐opening metathesis polymerization (ROMP)‐PNBs (Figure ), especially in metal‐catalyzed reactions. Recently, we have reported the risks of exposing the unsaturated ROMP scaffold to some metal complexes, and we have observed the insertion of the C=C double bond of ROMP‐PNB into a palladium–aryl complex, leading to the formation of an aryl‐substituted polymer . Considering the a priori attractive features of VA‐PNBs, we decided to test the behavior of the VA‐PNB skeleton as a support for palladium complexes in two cross‐coupling reactions, namely Suzuki and Negishi couplings.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the synthesis of ROMPH‐PNBs does not benefit from the advantage of the wide scope of the direct ROMP polymerization of substituted norbornenes, but affords a saturated and chemically robust scaffold. This has been shown for a stannylated ROMPH‐PNB, which has been used as support of the tin reagent in the palladium catalyzed Stille coupling . This work showed that this type of scaffold behaves in a similar way to the vinylic addition polynorbornenes which, being prepared in a lower number of steps, are a more convenient choice for catalytic applications.…”
Section: Vinylic Addition Polynorbornene (Va‐pnb) Vs Other Polynorbormentioning
confidence: 67%
“…We have also demonstrated that the disubstituted olefins of ROMP‐PNB do insert in Pd‐aryl bonds, becoming a potential reactive center in palladium‐catalyzed cross coupling reactions. The reaction of a ROMP‐PNB with the complex [PdBr(C 6 F 5 )(NCMe) 2 ] leads to the incorporation of the pentafluorophenyl group in the polymer backbone as clearly shown by 19 F NMR (Scheme ) …”
Section: Vinylic Addition Polynorbornene (Va‐pnb) Vs Other Polynorbormentioning
confidence: 99%
See 1 more Smart Citation
“…The marriage of these two chemistries required the polymerization of norbornene/cyclooctene derivatives-decorated with electrophilic α-bromo ester moieties that could undergo PPMs through reactions with nucleophilic thiols. The utility of pendant alkyl bromides has been illustrated for other substitution reactions as well [39][40][41][42][43][44][45]. Following our initial reports, we reasoned that this functionality may serve as a convenient handle to introduce other useful functional groups, such as acrylates and cinnamates; these are α,β-unsaturated carbonyls that can undergo further modifications through various Michael reactions, as well as photo-facilitated [2 + 2] cycloadditions.…”
Section: Introductionmentioning
confidence: 99%